2008
DOI: 10.1016/j.brainresbull.2007.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of vascular endothelial growth factor (VEGF) expression in motor neurons and its electrophysiological effects

Abstract: Previous studies have shown that VEGF expression in forebrain increases after experimental manipulations that increase neuronal activity [6,12]. One question is whether this also occurs in motor neurons. If so, it could be potentially advantageous from a therapeutic perspective, because VEGF prevents motor neuron degeneration [2,10,24]. Therefore, we asked whether endogenous VEGF expression in motor neurons could be modulated. We also asked what VEGF exposure would do to motor neurons using electrophysiology.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Our observations compare well with those of McCloskey et al [21] , who in a recent study demonstrated that exogenous exposure to VEGF at a concentration of 200 ng/ml under normal conditions depressed the stimulus-evoked depolarization of hypoglossal motor neurons. They considered this depression as a compensatory mechanism, failure of which would result in excessive firing of motor neurons and probable motor neuron loss comparable to that seen in ALS [21] . Thus, it is likely that addition of exogenous VEGF in normal cultures lowered the normal cellular, biochemical and physiological processes of the differentiated cells resulting in reduced ChAT expression.…”
supporting
confidence: 80%
“…Our observations compare well with those of McCloskey et al [21] , who in a recent study demonstrated that exogenous exposure to VEGF at a concentration of 200 ng/ml under normal conditions depressed the stimulus-evoked depolarization of hypoglossal motor neurons. They considered this depression as a compensatory mechanism, failure of which would result in excessive firing of motor neurons and probable motor neuron loss comparable to that seen in ALS [21] . Thus, it is likely that addition of exogenous VEGF in normal cultures lowered the normal cellular, biochemical and physiological processes of the differentiated cells resulting in reduced ChAT expression.…”
supporting
confidence: 80%
“…Another study reported a decreased VEGF level not only in neurons but also in astroglia in a rat EAE experimental model [53]. A VEGF decrease may be caused by neuronal dysfunction, as already demonstrated in epilepsy by McCloskey et al [54]. Astroglial production of VEGF is enhanced in pathological conditions, including human astrocytoma [55] and MS and EAE, to promote angiogenesis and glial survival [50].…”
Section: Angiogenesis In Eaementioning
confidence: 97%
“…Anti-VEGF clinical trials demonstrate huge variations in responses to long-term treatment, a portion of patients had a reduction in visual acuity. While this could be due to multiple factors, the so-called physiological levels of VEGF are most likely different from one patient to another, which are essential to protecting retinal cells and neurons and regulating neuronal function (35–41). In short, a suitable physiological level for one patient could potentially be harmful to retinal integrity in others.…”
Section: Lesson From Mg-specific Vegf Ko Mice: Implication For Antmentioning
confidence: 99%
“…Gene targeting analysis suggests that VEGF and semaphorins-mediated neuropilin-2 signaling is important to the migration of gonadotropin-releasing hormone neurons in the neuroendocrine system (53). VEGF has been suggested to reduce excessive excitation of hypoglossal motor neurons by downregulating stimulus-evoked depolarization, a critical mechanism to prevent ALS (35). VEGF is capable of downregulating synaptic responses significantly in hippocampal principal neurons in rats, which may be critical to the onset of epilepsy (36).…”
Section: Importance Of Vegf Signaling To Neuronal Function and Intmentioning
confidence: 99%